The Effects of Autogenic Relaxation on Blood Pressure in Patients with Hypertension - Istiqomah Istiqomah; Dwi Retnaningsih (Hippocratica : Journal of Modern Medicine and Healthcare Practice, 2026)
This empirical study examines the immediate cardiovascular shifts and neurovascular adaptations induced by autogenic relaxation in hospitalized adult patients diagnosed with essential hypertension. Utilizing a descriptive case approach with a structured pretest and posttest observational design, the research evaluated a participant cohort of five individuals undergoing concurrent pharmacological management. The nonpharmacological mind body intervention involved standardized standalone autogenic relaxation focusing on self induced somatic feelings of warmth and heaviness, administered once daily for twenty minutes across two consecutive days. Hemodynamic metrics were precisely captured using a calibrated manual sphygmomanometer and high sensitivity stethoscope to track immediate fluctuations resulting from minimized sympathetic hyperactivity. Quantitative results demonstrate consistent post intervention decompression, with systolic blood pressure decreasing by ten to fifteen millimeters of mercury and diastolic values dropping by five millimeters of mercury across all subjects. These uniform physiological reductions successfully shifted multiple participants into milder clinical hypertension categories without adverse secondary effects. The findings validate autogenic conditioning as a safe, effective, and reproducible complementary therapy capable of optimizing autonomic stability and enhancing target organ protection within contemporary medical surgical nursing frameworks.